BASKETBALL SHOOTING LEARNING MODEL FOR ELEMENTARY SCHOOL AGE 9-12 YEARS OLD - Zendy Praja; Ramdan Pelana; Widiastuti (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to develop a basketball shooting learning model for elementary school (SD) children aged 9-12 years, in order to produce an efficient and effective basketball shooting learning model for improving basketball shooting for elementary school (SD) children aged 9-12 years old. This research is a development research using Research and Development from Borg and Gall. To determine the effectiveness of the product, an implementation process was carried out using a pre-experimental research design in the form of "one group pretest-posttest design". The research subjects were 10 students of Duren Sawit Public Elementary School aged 9-12 years in Jakarta. The results of the product effectiveness test were carried out on 10 children / subjects. This research was conducted during the Covid-19 pandemic in 2020. This learning model as a whole was declared feasible and effective in developing and improving basketball shooting for elementary school children aged 9-12 years. The test instrument used was a test of basketball shooting skills and accuracy. Basketball shooting learning model for elementary school children aged 9-12 years has been declared valid both model and test instrument by two basketball experts and motor learning experts. Data analysis used the T-test formula. The data from the pretest and posttest shooting skills and the accuracy of shooting basketball used the Lilifors test at a significance level of = 0.05. The average score before treatment was 173.10 and after it was given it was 259.20, meaning that the average basketball shooting score was increasing. In the significance test of the difference with SPSS 26, the results of T-count = 13,249, df = 9 and p-value = 0.00 <0.05, which means that there is a significant difference in learning basketball shooting for elementary school children before and after the treatment of shooting basketball learning models, it can be said that the learning model for shooting basketball for elementary school children aged 9-12 years which is developed can effectively improve basketball shooting skills for elementary school children aged 9-12 years. The products of the research were in the form of manuals book and videos of basketball shooting learning models for elementary school children aged 9-12 years.